Growth and Phycocyanin Productitivity of Spirulina fusiformis under Various Light Regimes - Chrismadha, Tjandra; Waluya, Rizky Agus (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2013)
A blue green alga Spirulina fusiformis was grown under various light regimes in a laboratory scale experiment. A 500 watt halogen lamp was employed as the light source, while the light variation of 2,000 lux, 4,000 lux, 6,000 lux, 8,000 lux, and 10,000 lux was obtained by placing a series of 2 L experimental bottles at various distance. The growth medium used was modified Zarrouk medium with initial pH of 8.72, and room temperature was 28-30oC. After inoculation the alga was let to grow for 30 days, and observation on the biomass, chlorophyll, crude protein, and phycocyanin content were carried out every 10 days. The algal biomass was determined gravimetrically, the chlorophyll, phycocyanin, and protein content were measured using spectrophotometer after extraction in 90% aceton, pH 7.0 buffered water, and folin-phenol dye binding, respectively. The result shows a remarkable effect of light intensity to the algal biomass as well as the biochemical content. The specific growth rate increased from 0.08 doubling/day at light intensity 2,000 lux to 0.14 doubling/dat at 10,000 lux, which was equivalent to an increase in the biomass productivity of more than 3 times. The highest algal chlorophyll content was observed at light intensity between 4,000-8,000 lux, indicating the optimum light condition at that irradiance range. The protein content was consistently lower with light intensity, from 42.96-52.91% DW at 2,000 lux to 33.71-41.08 % at 10,000 lux. A consistent drop in the protein content also observed with the culture growth phase, from 39.82-52.91% DW in the early growth stage down to 33.71-42.96% at day 30. Light intensity in concomitance with the growth phase remarkably increase the algal phycocyanin content. In the early growth stage the phycocyanin content was ranged from 0.16% DW at 2,000 lux up to 1.229% DW at 10,000 lux, whereas at the end of the experiment the algal phycocyanin content were 1.04% DW and 2.436% DW, at 2,000 lux and 10,000 lux, respectively. It gave a consequence of more than 7 times higher phycocyanin productivity, which was from 0.09 mg/L/day at 2,000 lux to 0.62 mg/L/day at 10,000 lux. This result shows the importance of light factor in producing phycocyanin from the blue green alga Spirulina fusiformis.